Upaya Meningkatkan Kemampuan Menghafal Ayat-Ayat Al-Qur’an Hadis Menggunakan Media Disk Murattal Al-Qur’an pada Siswa MTs. Swasta Tarbiyah Waladiyah Pulau Banyak - Maulida Maulida; Nurmisdaramayani Nurmisdaramayani ; Neni Anggraini (Tarbiatuna: Journal of Islamic Education Studies, 2021)
Focus of this research is that the researcher focuses on the application of Murattal Disk Media and the efforts made by the teacher in the field of Al-Qur'an Hadith studies to improve students' reasoning abilities. 1). The effect of digital Al-qur'an-based Murattal Disk Media on students' reasoning abilities on the concept of understanding and memorizing verses of the Qur'an by students of Madrasah Tsanawiyah Private Tarbiyah Waladiyah Pulau Banyak which is significant is that the application of the model helps students to better understand the subject matter. 2). The improvement of students' reasoning abilities on indicators of creative thinking, flexible thinking, original thinking, and detailed thinking after the Murattal Disk Media was applied to students of Madrasah Tsanawiyah Swasta Tarbiyah Waladiyah Pulau Banyak. 3). Student activities when the Murattal Disk Media was applied to the field of study of Al-qur'an Hadith at the Private Tarbiyah Madrasah Waladiyah Pulau Banyak, namely the students responded well. The approach and type of research used in the preparation of this research tool was classroom action research, namely "researchers are trying to describe in detail the descriptive in the form of words by describing the main instrument in data collection. Efforts to Improve Ability to Memorize Al-Qur'an Hadith Verses Using Murattal Al-Qur'an Disk Media for MTs Students. Private Tarbiyah Waladiyah Pulau Banyak. The problems found in the research location are: 1). The learning and teaching process in madrasas, teachers in the field of Al-qur'an hadith studies have not involved students directly with the application of digital Al-qur'ans from the material in the field of Al-qur'an hadith studies that are taught so that students have not been trained in solving various problems in the field. study of the Qur'an and Hadith. 2). The unavailability of media that supports learning and teaching activities of the Qur'an Hadith in madrasas. In carrying out research on the efforts made to improve students' ability to understand the material of the short letter of the Qur'an in the subjects of Al-Qur'an Hadith Class VII MTs. Private Tarbiyah Waladiyah, of course, researchers find various factors that hinder the implementation of learning and research, but researchers believe that the inhibiting factors must be accompanied by supporting factors. In the implementation of research, the inhibiting and supporting factors vary greatly, especially in the implementation of research in each cycle. Keywords: Media, Murattal Disc, Comprehension